2004
DOI: 10.1542/peds.114.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral Implications of Habitual Snoring in Children

Abstract: PS seems to be associated with significant neurobehavioral deficits in a subset of children, possibly related to increased susceptibility to sleep fragmentation. Larger studies are urgently required because current guidelines for treatment of snoring in children may require reevaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
307
2
17

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 461 publications
(347 citation statements)
references
References 42 publications
21
307
2
17
Order By: Relevance
“…30 Previous studies have shown differences in the cognitive function of children with the obstructive sleep apnea syndrome, as compared with controls. 19,27,31 However, baseline cognitive scores of children with the obstructive sleep apnea syndrome fell within the normal range, a finding similar to that in the current study. Cognitive and behavioral abnormalities have been shown to be reduced after adenotonsillectomy in some, [24][25][26][27]29 but not all, 30 nonrandomized studies, with inconsistency in the reported effect after treatment.…”
Section: Discussionsupporting
confidence: 88%
“…30 Previous studies have shown differences in the cognitive function of children with the obstructive sleep apnea syndrome, as compared with controls. 19,27,31 However, baseline cognitive scores of children with the obstructive sleep apnea syndrome fell within the normal range, a finding similar to that in the current study. Cognitive and behavioral abnormalities have been shown to be reduced after adenotonsillectomy in some, [24][25][26][27]29 but not all, 30 nonrandomized studies, with inconsistency in the reported effect after treatment.…”
Section: Discussionsupporting
confidence: 88%
“…OSA in adults and children alike results in numerous complications, including cognitive dysfunction (Findley et al 1986;Gozal 1998;Beebe et al 2003;Archbold et al 2004). Indeed in children, sleep-disordered breathing has been associated with reduced cognitive function and general intelligence, as well as neuroimaging-based evidence for prefrontal cortical abnormalities (Schechter 2002;Gottlieb et al 2004;O'Brien et al 2004;Halbower et al 2006); severity of apnea also correlates with worsened neuropsychological deficits (O'Brien et al 2004). A caveat to utilizing OSA as a means to study the impact of sleep fragmentation is the difficulty in distinguishing the effect of sleep loss from that of poor oxygenation or even obesity, which could independently impair developmental processes.…”
Section: Negative Impacts Of Disrupted Sleep During Mammalian Developmentioning
confidence: 99%
“…ioral, and cardiovascular functions (5,7,8,11,13), the thresholds of disease severity that delineate the cost-benefit ratios for T&A, the primary line of treatment for pediatric SDB, are currently unknown. Thus, the recently published empirically based consensus guidelines that were developed for the treatment of SDB in children (12) do not mention any specific polysomnographic measures as firmly established criteria for T&A referral.…”
Section: Definition Of Abbreviationsmentioning
confidence: 99%
“…an AHI of more than 1 but less than 5 events/hour of sleep, even if such children are at risk for associated morbidity (13).…”
mentioning
confidence: 99%